AN ERROR ANALYSISN OF STUDENTS' SPEAKING ENGLISH PERFORMANCE (A STUDY (at the Second Semester of English Department in Institut Pendidikan Tapanuli Selatan) - Lesni aziza siregar Aziza Siregar (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: This research aims to know the students’ speaking English performance at the second semester of English department in Institut Pendidikan Tapanuli Selatan, the students’ errors in speaking English performance at the second semester of English department in Institut Pendidikan Tapanuli Selatan, and factors do the make students’ error in speaking English performance at the second semester of English department in Institut Pendidikan Tapanuli Selatan. The methodof this research is qualitative method. The data were gathered through triangulation, that is observation, interview and documentation at the second semester of English department in Institut Pendidikan Tapanuli Selatan. the writer conducted the observation in one class. The data were analyzed by data display, data reduction, and conclusion using some theories.The results are 1) The students’ speaking English performance is bad 2) The students’ speaking errors are in pronunciation are 57.35%, grammar are 23.52%, vocabulary are 4.415, and fluency are 14.70% but the most dominant errors with found in pronunciation. 3) the dominant factors which caused linguistic Keywords: Speaking English Performance, at the Second Semester of English Department in Institut Pendidikan Tapanuli Selatan. Abstrak: Penelitian ini bertujuan untuk mengetahui lebih luas bagaimana speaking English performance yang digunakan oleh mahasiswa semester dua program studi bahasa inggris di institut Pendidikan Tapanuli Selatan, Apa saja kesalahan yang dibuat mahasiswa di dalam speaking English performance di semester dua program studi bahasa inggris di Intstitut Pendididkan Tapanuli Selatan, dan apa penyebab kesalahan mahasiswa membuat kesalahan dalam speaking English performance di semester dua program studi bahasa inggris program studi bahasa inggris di Institut Pendidikan Tapanuli Selatan. Penelitian ini di lakukan dengan menggunakan metode kualitatif. Data didapatkan melalui triangulasi, yaitu observasi, wawancara, dan dokumentasi kepada mahasiswa semester dua program studi bahsa inggris di Institut Pendidikan Tapanuli Selatan. Data yang didapatkan menggunakan data display, data reduksi, dan penarikan kesimpulan. Hasil dari praktik mahasiswa dalam berbicara bahasa inggris adalah kesalahan dalam pengucapan kata 57.35, tata bahasa 23.52, kosakata 4.41, kepasihan 14.70, akan tetapi kesalahan yang dominant adalah pengucapan kata. Kata kunci: Bercicara Bahasa Inggris Secara Praktek, Mahasiswa Semester Dua